KERASULAN AWAM DAN TRANSFORMASI MASYARAKAT - Alexius Kurdo Irianto (Bahasa Indonesia, 2018)
Reality of the Church today requires adaptation of the Church to the world situation. Moreover, the Church as the People of God should be relevant to the situation of its members. Coaching and teaching needs to be adapted to the situation and needs of the people, so that helped people live their faith in their appropriate background. Therefore, we need a catechesis which involves the situation and needs of the people. Catechesis appropriate to the situation and needs of the people is known as contextual catechesis. Catechesis of contextual context emphasizes the people "there, and that time". What is the nature of contextual catechesis? How to build up the Church as the People of God? Globalization can make whosoever so focused and ignore the people's life around them. To overcome the individualistic attitude of the people of the Church, it needs to reemphasizes the importance of the Basic Ecclesial Communities among the people of the Churh. The Basic Ecclesial Community is a unit of Christians relatively small and easily gathered periodically to hear the word of God, a variety of daily problems, whether personal issues, groups or social problems, and finding solutions in the light of the Holy Scripture.